My problem is as follows (sorry, but the tags were giving me issues. I tried to make it as readable as possible): Let X have the pdf f(x)= θ * e-θx, 0 < x < ∞ Find pdf of Y = ex I've gone about this the way I normally do for these problems. I have G(y) = P(X < ln y) = ∫ θ * e-θx dx from 0 to ln y = 1 - y-θ So then I need g(y) = G'(y) of Y? which would be θ * e-θln y? I know there's something obvious in there that I'm missing. I'm having a hard time connecting the last equation to the process that I usually follow. If anyone can give a nudge, I'd be grateful.